Performance improvement of NES based on eddy current damping. (1st April 2023) - Dou, Jinxin; Yao, Hongliang; Cao, Yanbo; Li, Hui
Highlights: The eddy current damping (ECD) is applied to enhance the performance of the nonlinear energy sink (NES). The genetic algorithm is exploited to guide the parameter design. The vibration responses of the ECD enhanced NES are studied numerically. The good performance of the ECD enhanced NES is verified by experimental results. Abstract: This paper investigates the application of an eddy current damping (ECD) to improve the performance of a nonlinear energy sink (NES). The effect of the damping on the vibration suppression performance of the NES is presented. Next, the principle of the ECD is introduced and combined with the NES, namely ECD enhanced NES (ECD-NES). On this basis, the effect of the ECD-NES parameters on its vibration reduction performance is analyzed. Then, the proposed ECD-NES is applied to a cantilever beam system, and the vibration suppression performance of the ECD-NES is compared with that of the NES without ECD. An optimization strategy for the ECD-NES is proposed under the condition of comprehensive consideration of displacement control and energy dissipation. Lastly, the effectiveness of the ECD-NES is verified experimentally on the cantilever beam system. The results show that adding the ECD is effective in improving the performance of the NES. After ECD enhanced NES is installed, the amplitude decay speed is increased by 24.18% in simulations and 18.85% in experiments; the energy dissipation rate is increased by 7.3% compared with the NES without ECD.